2021
DOI: 10.1186/s12889-021-11975-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related consequences of the type and utilization rates of electronic devices by college students

Abstract: Background College students are leading an evolution of device use both in the type of device and the frequency of use. They have transitioned from desktop stations to laptops, tablets, and especially smartphones and use them throughout the day and into the night. Methods Using a 35-min online survey, we sought to understand how technology daily usage patterns, device types, and postures affect pain and discomfort to understand how knowledge of tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…25 The need to use technology to attend classes virtually might affect different aspects of posture. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The need to use technology to attend classes virtually might affect different aspects of posture. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Benden et al. 26 have argued that the changes in workspaces brought about by COVID-19 might have exacerbated postural problems in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A survey executed by Jacob Pausher (2016) in 2015, discovered three-quarters of adults in 40 countries procured access to the internet at least once a day, and several times daily in some countries [ 17 ], and also, the social media was more often perused in developing countries than in developed countries. Study by Benden et al in 2021 also showed that smartphones as their most frequently used technology (64.0%), followed by laptops and tablets (both 53.2%), and desktop computers (46.4%) [ 18 ]. In addition, as observed by Alzhrani et al in 2019, 97.5% of 398 university employees and research students used smartphones for both work and personal reasons (72.1%), 1.8% for work alone, and 23.6% for personal use only [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…et al , in 2017 about mobile touch screen devices’ (MTSDs) operators alleged the amount, features, tasks and positions of device use had limited evidence regarding musculoskeletal symptoms and exposures [ 22 ]. Study by Benden also showed that the participants were more likely to adopt non-traditional workplace postures as they used these devices primarily on the couch or at a chair with no desk [ 18 ].…”
Section: Discussionmentioning
confidence: 99%